The Determinants of the Variability of Stock Prices - Japanese Evidence - Tarazi, Ramzi E. N. (2011)
This study examines the ability of fundamental variables and macroeconomics variables data to explain future stock market returns of Japan companies by looking at how price-earnings (P/E) ratio, book-to-market (B/M) ratio, current ratio, return on assets (ROA), inflation, changes in interest rates and changes in exchange rates influence future stock market returns. The sample size for the study is 3808 companies, listed on Tokyo stock exchange as of 2010. Data is collected during a period of eleven years, from 2000 to 2010. To test the hypotheses between dependent and independent variables, regression and correlation results are derived through the EVIEWS. Findings show strong and significant correlations between stock return and B/M ratio, P/E ratio, ROA, inflation, changes in interest rates and changes in exchange rates.